0% found this document useful (0 votes)
48 views

Matrix Algebra Solution To Simultaneous Algebraic Equations - Gauss Elimination Method

1) The document describes the Gauss elimination method for solving simultaneous algebraic equations. It involves writing the equations in matrix form and then performing row operations to eliminate variables until an upper triangular matrix is obtained. 2) The elimination of variables is done in stages, starting with the first variable. At each stage, row operations are performed to make one matrix element a pivot and eliminate the corresponding variable from other rows. 3) After obtaining an upper triangular matrix, the values of the variables are determined by back substitution, starting with the last equation and working backwards.

Uploaded by

varshasdm1987
Copyright
© © All Rights Reserved
Available Formats
Download as PDF, TXT or read online on Scribd
0% found this document useful (0 votes)
48 views

Matrix Algebra Solution To Simultaneous Algebraic Equations - Gauss Elimination Method

1) The document describes the Gauss elimination method for solving simultaneous algebraic equations. It involves writing the equations in matrix form and then performing row operations to eliminate variables until an upper triangular matrix is obtained. 2) The elimination of variables is done in stages, starting with the first variable. At each stage, row operations are performed to make one matrix element a pivot and eliminate the corresponding variable from other rows. 3) After obtaining an upper triangular matrix, the values of the variables are determined by back substitution, starting with the last equation and working backwards.

Uploaded by

varshasdm1987
Copyright
© © All Rights Reserved
Available Formats
Download as PDF, TXT or read online on Scribd
You are on page 1/ 11

1

Matrix Algebra

Solution to Simultaneous Algebraic Equations Gauss Elimination
Method:

Consider n simultaneous equations ,
a
11
x
1
+ a
12
x
2
+, a
13
x
3
+ a
1n
x
n
= b
1
a
21
x
1
+ a
22
x
2
+ a
23
x
3
+ a
2n
x
n
= b
2

a
31
x
1
+ a
32
x
2
+ a
33
x
3
+ a
3n
x
n
= b
3


a
n1
x
1
+ a
n2
x
2
+ a
n3
x
3
+ a
nn
x
n
= b
n

write the given set of equations in matrix form,





=






In Gauss elimination method the variables x
2
, x
n-1
, will be
successively eliminated using Row Operations. This step is called forward elimination
. The given matrix will be converted to into an upper triangular matrix, Lower triangular
elements become zeros.
After forward elimination the n
th
equation (last equation) become simple , it as an
equation with one variable x
n
, determine x
n
. Now using (n-1)
th
equation x
n-1
can be
determined. Similarly using (n-2)
nd
equation x
n-2
can be determined. Using (n-3)
rd

equation x
n-3
can be determined. Continue up to first equation until all the unknowns are
determined. This is called backward substitution.

Forward Elimination
Step 1 : a
11
becomes pivot, eliminate x
1
from row2 , row3, row4, row n etc

Row2 a
21
= a
21
- ( a
21
/ a
11
) a
11
a
21
becomes 0


a
22
= a
22
- ( a
21
/ a
11
) a
12
a
22
changes


a
23
= a
23
- ( a
21
/ a
11
) a
13
a
23
changes

x
1

x
2

x
3





x
n

a
11
a
12
a
13
. a
1n

a
21
a
22
a
23
. a
2n

a
31
a
32
a
33
. a
3n

.
.
.
.
.
.
.
.

.
.
.
.
.
.
.
.

a
n1
a
n2
a
n3
. a
nn

b
1
b
2

b
3





b
n


2



etc up to a
1n
= a
2n
- ( a
21
/ a
11
) a
1n
a
2n
changes




b
2
= b
2
- ( a
21
/ a
11
) b
1
b
2
changes
whatever we did to make a
21
= 0 applied the same to other elements
of that row

Row3 a
31
= a
31
- ( a
31
/ a
11
) a
11
a
31
becomes 0


a
32
= a
32
- ( a
31
/ a
11
) a
12
a
32
changes


a
33
= a
33
- ( a
31
/ a
11
) a
13
a
33
changes


etc up to a
3n
= a
3n
- ( a
31
/ a
11
) a
1n
a
3n
changes


b
3
= b
3
- ( a
31
/ a
11
) b
1
b
3
changes
whatever we did to make a
31
= 0 applied the same to other elements
of that row





Row n a
n1
= a
n1
- ( a
n1
/ a
11
) a
11
a
n1
becomes 0


a
n2
= a
n2
- ( a
n1
/ a
11
) a
12
a
n2
changes


a
n3
= a
n3
- ( a
n1
/ a
11
) a
13
a
n3
changes


etc up to a
nn
= a
nn
- ( a
n1
/ a
11
) a
1n
a
nn
changes


b
3
= b
3
- ( a
31
/ a
11
) b
1
b
3
changes
whatever we did to make a
n1
= 0 applied the same to other elements of that row.

Now, re-write the whole matrix equation. First row remains same, elements of other
rows will be different.

Step2 : : a
22
becomes pivot, eliminate x
2
from row3 , row4, row5, etc., row n
following the same method
Now, re-write the whole matrix equation. First row , Second row remains same,
elements of other rows will be different

Step3 : : a
33
becomes pivot, eliminate x
3
from row4 , row5, row6, etc., row n
following the same method
Now, re-write the whole matrix equation. First row , Second row , Third row remains
same, elements of other rows will be different

Continue until the variables x
2
, x
3
, x
4
. x
n-1
will be
successively eliminated and all the lower triangular elements becomes zero.

3

Backward substitution.
After forward elimination the n
th
equation (last equation) become simple , it as an
equation with one variable x
n
, determine x
n
. Now , using (n-1)
th
equation x
n-1
can be
determined. Similarly using (n-2)
nd
equation x
n-2
can be determined. Using (n-3)
rd

equation x
n-3
can be determined. Continue up to first equation until all the unknowns are
determined. The method is best understood by solving problems.



Different Methods used to Solve Set of Simultaneous Equations in FEM.

Method of Matrix Inversion
Gauss elimination method
Cholesky Decomposition Technique
Gauss-Seidal Iteration Technique
Relaxation Method

Numerical examples illustrating Gauss elimination method :

Problem 1. Solve the following set of equation by Gaussian elimination
technique.

5x1 + 3x2 + 2x3 + x4 = 4
4x1 + 3x2 - 3x3 - 2x4 = 5
x1 + 2x2 - 2x3 + 3x4 = 6
-4x1 + 3x2 5x3 + 2x4 = 7

Solution : Write the given equations in Matrix Form













[ CO ] [ X ] = [ CONS ]
[ a ] [ x ] = [ b ]
5 3 2 1



*
x1



=
4
4 3 -3 -2 x2 5
1 2 -2 3 x3 6
-4 3 -5 2 x4 7

4

Step 1 : a
i j
= a
i j
(a
i1
/ a
11
) a
1j
b
i
= b
i
(a
i1
/ a
11
) b
1

i = 2, j = 1,2,3,4

Row 2 i = 2 j = 1,2,3,4
4 (4/5) 5 = 4 (4) = 0.0 3 (4/5) 3 = 3 2.4 = 0.6
-3 (4/5)2 = -3 1.6 = -4.6 -2 (4/5) 1 = -2 0.8 = -2.8

Row 3 i = 3 j = 1,2,3,4
1 (1/5)5 = 1 1 = 0.0 2 (1/5)3 = 2 -0 .6 = 1.4

-2 (1/5) 2 = -2 0.4= -2.4 3 (1/5) 1 = 3 0.2 = 2.8

Row 4 : i = 4 j = 1,2,3,4
-4 ( -4 / 5)5 = 4 - 4 = 0 3 ( -4 / 5)3 = 3+2.4 = 5.4
-5 ( -4 /5) 2 = -5 + 1.6 = -3 .4 2 ( -4 /5) 1 = 3 0.2 = 2.8

b i = b i (a i1/ a11) b 1
i = 2 b2 = 5 (4/5)4 = 1.8
i = 3 b3 = 6 (1/5)4 = 5.2
i = 4 b4 = 7 (-4/5)4 = 10.2

The modified matrix equation , after eliminating x1
from 2nd , 3rd and 4th equations.



















5 3 2 1



*
x1



=
4
0 0.6 -4.6 -2.8 x2 1.8
0 1.4 -2.4 2.8 x3 5.2
0 5.4 -3.4 2.8 x4 10.2

5

Step 2 : To eliminate x2 from Row 3 and Row 4
a
i j
= a
i j
(a
i2
/ a
22
) a
2j
b
i
= b
i
(a
i2
/ a
22
) b
2
i = 3, j = 2,3,4

Row 3 i =3 j = 2,3,4
1.4 (1.4/0.6) 0.6 =1.4 1.4 = 0.0 j = 2
-2.4 (1.4/0.6) (-4.6) = 2.4+10.73 =8.33 j = 3
2.8 (1.4/0.6)(-2.8) = -2.8 6.53 = 9.33 j = 4

Row 4 i = 4 j = 2,3,4

5.4 (5.4/0.6)0.6 = 5.4-5.4 = 0.0 j = 2
-3.4 (5.4/0.6)(-4.6) = -3.4+41.4 = 38 j = 3
2.8 (5.4/0.6)2.8 = 2.8 +25.2 = 28 j = 4

b i = b i (a i2/ a22) b 2

i = 3 b3 = b3 (a32/a22)b2
5.2 - (1.4/0.6) 1.8 = 5.2 4.2 = 1

i = 4 b4 = b4 (a42/a22)b2
10.2 - (5.4/0.6)1.8 = 10.2 -16.2 = -6

The modified matrix after step 2 eliminating x2 from 3rd and 4th equations.














Step 3 : To eliminate x3 from Row 4
a
i j
= a
i j
(a
i3
/ a
33
) a
3j
b
i
= b
i
(a
i3
/ a
33
) b
3
i = 4, j = 3,4

a43 = a43 (a43/ a33) a33 = 38 (38 / 8.33) 8.33 = 38 38 = 0.0

5 3 2 1



*
x1



=
4
0 0.6 -4.6 -2.8 x2 1.8
0 0 8.33 9.32 x3 1
0 0 38 28 x4 -6

6


a44 = a44- (a43/ a33) a34 = 28 - (38 / 8.33) 9.32
= 28 42.52 = -1 4.52

b i = b i (a i3/ a33) b 3 i = 4,
b4 = b4 - (a43/ a33) b3 b4 = -6 - (38 / 8.33) 1 = - 6 - 4.56 = - 10.56
The modified matrix, after step 3 , eliminating x3 from 4th equation.













Back Substitution:

The modified equations are

5 x1 + 3 x2 + 2 x3 + x4 = 4
0.6 x2 4.6 x3 - 2.8 x4 = 1.8
8.33 x3 + 9.32 x4 = 1
-14.52 x4 = -10.56
x4 = ( -1 0.56/ -1 4.52) = 0.727

8.33 x3 + 9.32 (0.727 ) = 1
x3 = (1 - 6.776) / 8.33 = - 0.693

0.6 x2 4.6( - 0.693) -2.8 (0.727) = 1.8
0.6 x2 = (1.8 - 3.1878 + 2.0356)
x2 = (1.8 - 3.1878 + 2.0356) / 0.6 = 1.079

5x1 + 3 (1.079) + 2 ( - 0.693) + 0.727 = 4
x1 = ( 4 - 3 (1.079) + 2 (0.693) - 0.727 ) / 5 = 0.155

x1= 0.155 x2=1.079 x3= - 0.693 x4= 0.727
5 3 2 1



*
x1



=
4
0 0.6 -4.6 -2.8 x2 1.8
0 0 8.33 9.32 x3 1
0 0 0 -
14.52
x4 -
10.56

7


Prob2 : Solve using gauss elimination method

x1- 2x2 + 6 x3 = 0 2x1 +2x2 + 3x3 = 3 -x 1 + 3x2 = 2



=



Step 1 : a

i j
= a
i j
(a
i1
/ a
11
) a
1j
I = 2,3 j = 2,3

2- (2/1)* 1 = 0 2 (2/1) (-2) = 6 3 (2/1) (6) = -9
-1- (-1/1) 1 = 0 3 (-1/1) (-2) = 1 0 (-1/1) 6 = 6

b
i
= b
i
- (a
i1
/ a
11
) b
1


3 (2/1) *0 = 3 2 (-1/1) *0 = 2

Modified Matrix After step1



=





Step 2 : a
i j
= a
i j
(a
i2
/ a
22
) a
2j
i = 3 j = 2,3
1 (1/6)* (6) = 0 6 (1/6) (-9) = 7.5

b
i
= b
i
- (a
i2
/ a
22
) b
2

2 (1/6) 3 = 1.5


x1
x2
x3
1 -2 6
2 2 3
-1 3 0
0
3
2
x1
x2
x3
1 -2 6
0 6 -9
0 1 6
0
3
2

8




Modified Matrix After step2



=




Back Substitution :
7.5 x3 = 1.5 x3 = 1.5 / 7.5 = 0.2 x3 = 0.2

6 x2 9x3 = 3 x2=(3 + 9(0.2))/6 =0.8 x2 = 0.8

x1 2x2 +6x3 = 0 x1 = 2(0.8)6(0.2) = 0.4 x1 = 0.4


Prob 3 :Solve using gauss elimination method
4x1 +6x2 +8x3 = 2 8x1 +4x2 + 6x3 = 4 6x1 + 2x2+4x3= 6

Solution : writing the equations in matrix form


=





Step 1 : a
i j
= a
i j
(a
i1
/ a
11
) a
1j
i = 2,3 j = 2,3

8 - (8/4)* 4 = 0 4 (8/4) (6) = -8 6 -( 8/4)8 = -10
6 -( 6/4) 4 = 0 2 (6/4 (6) = -7 4 (6 /4) 8 = -8

b
i
= b
i
- (a
i1
/ a
11
) b
1

4 (8/4) 2 = 0 6 (6/4) 2 = 3
x1
x2
x3
1 -2 6
0 6 -9
0 0 7.5
0
3
1.5
4 6 8
8 4 6
6 2 4
x1
x2
x3
2
4
6

9


Modified matrix equation after step 1


=




Step 2 : a
i j
= a
i j
(a
i2
/ a
22
) a
2j
i = 3 j = 2,3

-7 (-7/-8) (-8) = 0
-8 -(-7 / -8 )( -10) = -8 +70/8 = -8 + 8.75 = 0.75

b
i
= b
i
- (a
i2
/ a
22
) b
2

3 (-7/-8) 0 = 3

Modified matrix equation after step 2 :








0.75 x3 = 3 x3 = 3/0.75 = 4 x3 = 4

-8 x2 -10 x3 = 0 -8x2 -10 (4) = 0 -8x2 = 40 x2 = -5

4x1+6x2 + 8x3 = 2 4x1+ 6(-5) +8(4) = 2

x1 = (2+30 -32 ) / 4 =0

x1 = 0 x2 = -5 x3= 4



4 6 8
0 -8 -10
0 -7 -8
X1
X2
X3
2
0
3
4 6 8
0 -8 -10
0 0 0.75
X1
X2
x3
2
0
3

10



Prob 4 : Solve using gauss elimination method
3x1 -3x2 -2x3 = 5 2x1+2x2+3x3= 6 3x1 - 5x2+2x3= 7





Step 1 :
a
i j
= a
i j
(a
i1
/ a
11
) a
1j
i = 2,3 j = 2,3
2 - (2/3)3 = 0 2 - (2/3)(-3) = 4 3 -( 2/3)(-2) = 4.33
3 -( 3/3) 3 = 0 -5 (3/3 (-3) = -2 2 (3/3)(-2) = 4

b
i
= b
i
- (a
i1
/ a
11
) b
1

6 (2/3) 5 = 6-10/3 = 2.667 7 (3/3) 5 = 2
Modified matrix is





Step 2 :
a
i j
= a
i j
(a
i2
/ a
22
) a
2j
i = 3 j = 2,3
-2 - (-2/4)4 = 0 4 - (-2/4)(4.333) = 4+ 2.166 = 6.166

b
i
= b
i
- (a
i2
/ a
22
) b
2

2 (-2/4) 2.667 = 2+(2.667/2) = 2+1.333 = 3.333





6.166 x3 = 3.333 x3 = ( 3.333/6.166) = 0.504

4x2 + 4.333x3 = 2.667 4x2 = 2.667 - 4.333 (0.504)
x2 = 0.483 /4 = 0.120

3 -3 -2 5
2 2 3 6
3 -5 2 7
3 -3 -2 5
0 4 4.33 2.667
0 -2 4 2
3 -3 -2 5
0 4 4.33 2.667
0 0 6.166 3.333

11


3x1 -3x2 2x3 = 5 3x1 -3(0.120) -2(0.504) = 5
x1 = (5 + 0.360 +1.008) / 3 = 2.122

x1 = 2.122 x2 = 0.120 x3 = 0.504


THUS COMPLETE GAUSSIAN ELIMINATION
TECHNIQUE

You might also like